Correction of Hypercoagulation in Pregnant Women, by Using Intermittent Plasmapheresis in Combination with 10% HES - T. A. Fedorova; O. V. Rogachevsky; A. S. Ochan (Общая реаниматология)
Objective: to evaluate the impact of intermittent plasmapheresis in combination with 10% HES (Refortan® HES 10%, Berlin-Chemie AG) on hemostatic parameters in pregnant women with hypercoagulation syndrome. Subjects and methods. One hundred and forty pregnant women at 25-to-34 weeks gestational age with significant hypercoagulation as shown by hemostasiograms, who received a course of intermittent plasmapheresis for correction of hemostasis, were followed up. Plasma exchange using 10% HES (Refortan®) 500 ml was performed in 80 pregnant women. That with 0.9% NaCl 800 ml was carried out in 60 pregnant women. Results. There were substantial shifts towards a reduced coagulation potential in both groups. When a control hemostasiogram was recorded after 14 days, no negative changes were found in the former group whereas in the latter group all the study indices returned to the values obtained before a course of intermittent plasma-pheresis with plasma exchange using 0.9% NaCl. Conclusion. The performed analysis of hemostatic changes in pregnant women from the study and control groups leads to the conclusion that the use of HES (Refortan® 10%) as a plasma-substituting solution during intermittent plasmapheresis results in a more considerable and longer stabilization of the blood coagulation potential at the expense of the plasma and platelet links of hemostasis and the increased blood fibrinolytic potential, as suggested by the indicators of decreased intravascular coagulation processes. Furthermore, these positive effects persist for at least two weeks, which promotes a more effective prevention of placental insufficiency and gives grounds to substantially reduce a medical burden in pregnant women with hypercoagulation syndrome and to prolong pregnancy in these women. Key words: pregnancy, miscarriage, hypercoagulation, plasmapheresis, hydroxyethyl starch.